An innovation story: Irrigated banana value chain development in Ethiopia - International Livestock Research Institute (International Livestock Research Institute, 2011)
This innovation story narrates the experience of Improving Productivity and Market Success (IPMS) project on innovative banana value chain development in Metema district, Amhara, Ethiopia. The project introduced banana production systems in the district for the first time in 2005. IPMS together with the stakeholders provided support along the banana value chain on production, in put supply and marketing.